2014
DOI: 10.1089/jwh.2013.4569
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Practices Among First-Generation Immigrant Muslim Women

Abstract: Background: The purpose of this study was to identify beliefs about breast cancer, screening practices, and factors associated with mammography use among first-generation immigrant Muslim women in Chicago, IL. Methods: A convenience sample of 207 first-generation immigrant Muslim women (Middle Eastern 51%; South Asian 49%) completed a culturally adapted questionnaire developed from established instruments. The questionnaire was administered in Urdu, Hindi, Arabic, or English, based on participant preference. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 53 publications
1
63
2
Order By: Relevance
“…While biennial mammography rates in our sample are lower than the Healthy 2020 target of 81.1 %, our sample had screening mammography rates greater than those reported in prior Muslim samples [20, 22]. One of these prior studies was conducted in Greater Chicago [20], and it may be that increased awareness of breast cancer screening in the community explains our higher rates.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…While biennial mammography rates in our sample are lower than the Healthy 2020 target of 81.1 %, our sample had screening mammography rates greater than those reported in prior Muslim samples [20, 22]. One of these prior studies was conducted in Greater Chicago [20], and it may be that increased awareness of breast cancer screening in the community explains our higher rates.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, a Chicago-based survey of 215 Arab and South Asian Muslim women over 40 reported 52 % of respondents had a mammogram in the previous 2 years [20], similar to the 54 % rate found in a California-based study of 180 Muslims [22]. Studies of Iranian women in California note rates between 47 and 81 % of respondents having screening mammography in the past year [21, 22].…”
Section: Introductionmentioning
confidence: 78%
“…It should be noted that the relationship between age, educational levels, marital status, English proficiency, and breast cancer screening practices observed in our study was inconsistent with the findings of previous studies, particularly in the United States, which have indicated that factors, such as comparatively younger age, having higher educational levels, being married, and having better English proficiency, were significantly associated with a greater rate of breast cancer screening practices among Arabic women. 20,21 Our findings indicate that in Australia barriers, such as cultural health beliefs and practices, rather than demographic characteristics, influence Arabic women's screening behaviors more strongly. Further research on exploring this score is warranted.…”
Section: N Discussionmentioning
confidence: 74%
“…Interestingly, a similar relationship was not found in the case of CBE and mammography, a feature that is inconsistent with the situation among Arabic women in the United States. 20,21 The reason may be that compared with CBE and mammography the practice of breast awareness is less embarrassing because it does not demand the exposure of the body to a stranger. Consistent with other studies, 21,33 the Arabic version of the BSCQB indicated an association between employment status and mammography.…”
Section: N Discussionmentioning
confidence: 99%
“…Cancer screening and management: Studies reviewed under this category typically focused on breast and/or cervical cancer (n = 10; Hasnain, Menon, Ferrans, & Szalacha, 2014;Haworth, Margalit, Ross, Nepal, & Soliman, 2014;K. E. Kim et al, 2014;Kue, Zukoski, Keon, & Thorburn, 2014;Monnat, 2014;A.…”
Section: Resultsmentioning
confidence: 99%